Recent Trends in Southern Wage Differentials - Fuchs, Victor R.; Perlman, Richard (The Review of Economics and Statistics, 1960)
A HIGH birth rate, a declining demand for labor in agriculture, and poor educational facilities have traditionally provided the South with a relatively large supply of untrained labor for manufacturing industries. This condition suggests the following hypotheses: i. Average wages in manufacturing will be relatively low in the South because the southern industrial structure will tend to be heavily weighted with low-wage (low-skilled) industries. 2. Because labor and capital are not perfectly mobile, southern wages will tend to be lower than elsewhere for identical work. 3. For the same reasons of excess supply and incomplete mobility, southern wages will be particularly low for work requiring little skill and training. 4. Because of the wage differential, the South should be gaining in manufacturing relative to the rest of the country. 5. Because the differential is greater in lowwage employment, the South should be gaining most in those industries which make the greatest use of low-wage labor. The purpose of this paper is to test these hypotheses and to draw conclusions regarding the balance of forces which tend, on the one hand, to eliminate regional wage differentials, and on the other hand, to perpetuate them. In addition to examining shifts in the location of manufacturing, we will consider the influence of population change and minimum wage legislation on the southern wage position.